2011
DOI: 10.1590/s1516-635x2011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of floor type (dirt or concrete) on litter quality, house environmental conditions, and performance of broilers

Abstract: This study was conducted with the objective of evaluating the use of concrete or hard-packed dirt floor in broiler houses. This experiment was carried out in two different phases. The following performance parameters were studied: live weight, feed intake, feed conversion ratio, and mortality. Litter moisture, pH and temperature were measured. Litter residual contamination after cleaning and disinfection was also evaluated. A dry bulb thermometer, a wet bulb thermometer, and a black bulb thermometer were place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
1
13
4
1
Order By: Relevance
“…Blue curtains were selected in the more parsimonious model, explaining lower mortality (although not significant) and birds raised in houses with blue curtains achieved a significantly better cFCR than those raised in houses equipped with yellow curtains. Present results are in contradiction with those obtained by (Abreu et al, 2011), who found that broilers reared in houses with yellow curtains presented on average the best FCR (although this depended on flock, season and lighting program). The main difference between studies relies on the number of birds; while Abreu et al (2011) conducted their study on experimental conditions (200 birds per flock, n=6), we used a more realistic approach by providing data on commercial houses.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Blue curtains were selected in the more parsimonious model, explaining lower mortality (although not significant) and birds raised in houses with blue curtains achieved a significantly better cFCR than those raised in houses equipped with yellow curtains. Present results are in contradiction with those obtained by (Abreu et al, 2011), who found that broilers reared in houses with yellow curtains presented on average the best FCR (although this depended on flock, season and lighting program). The main difference between studies relies on the number of birds; while Abreu et al (2011) conducted their study on experimental conditions (200 birds per flock, n=6), we used a more realistic approach by providing data on commercial houses.…”
Section: Discussioncontrasting
confidence: 99%
“…Curtains: Although the curtain colors could, at first, appear anecdotic, some studies highlighted its importance on birds' growth and welfare (Olanrewaju et al, 2006;Abreu et al, 2011). Blue curtains were selected in the more parsimonious model, explaining lower mortality (although not significant) and birds raised in houses with blue curtains achieved a significantly better cFCR than those raised in houses equipped with yellow curtains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some production facilities utilize concrete floors in broiler houses, while others employ hard-packed dirt. It seems intuitive that concrete floors would decrease leaching of contaminates into the soil below, and while this floor type increases building costs it may also positively affect bird health by decreasing mortality without impacting live bird performance(Abreu et al 2011). The European Union also requires a total house clean-out between each grow-out, which would be a mitigating management strategy to avoid build-up of potential pollutants (EU-Council 2007).…”
mentioning
confidence: 99%
“…Nitrogen yang pada dasarnya bersifat basa, akan meningkatkan pH apabila bercampur dengan litter. Abreu et al (2011) menyatakan bahwa tingginya kandungan N ekskreta yang terdapat pada litter dapat memicu peningkatan pH litter. N ekskreta dalam bentuk uric acid akan dikonversi oleh bakteri ureolitik dengan didukung kondisi lingkungan (H2O dan O2) sehingga menghasilkan NH3 dan CO2.…”
Section: Ph Litterunclassified